Circadian expression of the maize catalase Cat3 gene is highly conserved among diverse maize genotypes with structurally different promoters. - Polidoros, A N (1998)
The Cat3 gene of maize exhibits a transcriptionally regulated circadian rhythm. In the present study we examined the following: (1) the extent of the circadian Cat3 expression between maize genotypes of diverse origin; (2) the functional significance of a Tourist transposable element located in the Cat3 promoter of the inbred line W64A, which harbors putative regulatory elements (GATA repeat, CCAAT boxes) shown to be involved in the light induction and circadian regulation of the Arabidopsis CAB2, as well as other plant genes; and (3) aspects of the physiological role of CAT-3 in maize metabolism. Results confirm that the circadian Cat3 expression is a general phenomenon in maize. Regulation of Cat3 gene expression is not dependent on the presence of the Tourist element in the promoter of the gene nor on the presence of motifs similar to those found significant in the circadian expression of the Arabidopsis CAB2 gene. Structural diversity was revealed in the Cat3 promoters of maize genotypes of diverse origins. However, highly conserved regions with putative regulatory motifs were identified. Relevance of the conserved regions to the circadian regulation of the gene is discussed. Possible physiological roles of CAT-3 are suggested.